(3ebGeGJ GHf MehjIs - (3GdUGMH CHh GdeXaQ aNQ GdOjf jhSa Hf eMeO (B( (3UOQ GdOjf(B) (3Hf YeQ GHf Ydj Hf eMeO Hf MehjI GdLhjfi,J (B647 (3g` s ((3YHOGdQGRb GdedG eMeO GdMGL adjM GdHZOGOj s)
(3ChdgG (B:s
(3bGd GdCejQ GdCLqd GHf MehjI GdLhjfj Gddge Efc CeQJfG aeG GFJeQfG s
(3BNQgG (B:s
(3Udi Ydjg Gddg eG fSN GdOLi UHM heG dHi GdMLjL hcqHQG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQ aj GdLRA GdChd GdQbejf (B145-146 (3COHs
(3cJHJ Yf fSNI cGXe GdfLaj GdJj cJHgG SfI (B1352(3g```s
(3hGdJj cJHJ Yf fSNI ecJhHI SfI (B1301(3g```s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdCOHs